Genomic Diversity, Virulence Gene, and Prophage Arrays of Bovine and Human Shiga Toxigenic and Enteropathogenic Escherichia coli Strains Isolated in Hungary - Sváb, Domonkos; Falgenhauer, Linda; Mag, Tünde; Chakraborty, Trinad; Tóth, István (Frontiers in Microbiology, 2022)
Escherichia coli belonging to the enterohemorrhagic (EHEC), Shiga toxin-producing (STEC) and atypical enteropathogenic (aEPEC) pathotypes are significant foodborne zoonotic pathogens posing serious health risks, with healthy cattle as their main reservoir. A representative sampling of Hungarian cattle farms during 2017-2018 yielded a prevalence of 6.5% and 5.8% for STEC and aEPEC out of 309 samples. The draft genomes of twelve STEC (of them 9 EHEC), and four aEPEC of bovine origin were determined. For comparative purposes we also included 3 EHEC and 2 aEPEC strains of human origin, as well four commensal isolates and one extraintestinal pathogenic E. coli (ExPEC) obtained from animals in a final set of 26 strains for a WGS based analysis. Apart from key virulence genes, these isolates harbored several additional virulence genes with arrays characteristic for the site of isolation. The most frequent insertion site of Shiga toxin (stx) encoding prophages was yehV for the Stx1 prophage and wrbA and sbcB for Stx2. For O157:H7 strains, the locus of enterocyte effacement (LEE) pathogenicity island was present at the selC site, with integration at pheV for other serotypes, and pheU in the case of O26:H11 strains. Several LEE-negative STEC and aEPEC as well as commensal isolates carried additional prophages, with an average of ten prophage regions per isolate. Comparative phylogenomic analysis showed no clear separation between bovine and human lineages among the isolates characterized in the current study. Similarities in virulence gene arrays and close phylogenetic relations of bovine and human isolates underline the zoonotic potential of bovine aEPEC and STEC and emphasize the need for frequent monitoring of these pathogens in livestock.